2001
DOI: 10.1164/ajrccm.164.6.2102125
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Airflow Obstruction, Proliferation of Abnormal Smooth Muscle Cells, and Impairment of Gas Exchange as Predictors of Outcome in Lymphangioleiomyomatosis

Abstract: Lymphangioleiomyomatosis (LAM) is a rare disease, occurring in women, characterized by cystic degeneration of the lungs, abdominal tumors, and proliferation of abnormal smooth muscle cells. Lung function abnormalities consist of impairment of the diffusion capacity (DL(CO)) and airflow obstruction. The objective of this study was to correlate the functional impairment with histologic measures of disease severity to identify predictors of disease outcome. Lung function of 143 patients and lung biopsies of 74 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
4
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 11 publications
10
101
4
7
Order By: Relevance
“…Further, a positive response to bronchodilators was a predictor of decline in Dlco after adjusting for FEV 1 /FVC ratio. This finding differs from those reported in our previous study 9 in which we found a relationship between a positive bronchodilator response to albuterol, the predominance of LAM cell proliferation, and an accelerated decline in FEV 1 but not in Dlco. However, the fact that a response to bronchodilators is now shown to be associated with a greater rate of Dlco decline is not surprising.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Further, a positive response to bronchodilators was a predictor of decline in Dlco after adjusting for FEV 1 /FVC ratio. This finding differs from those reported in our previous study 9 in which we found a relationship between a positive bronchodilator response to albuterol, the predominance of LAM cell proliferation, and an accelerated decline in FEV 1 but not in Dlco. However, the fact that a response to bronchodilators is now shown to be associated with a greater rate of Dlco decline is not surprising.…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement, 9 the proportion of positive responses to ␤-adrenergic bronchodilators was found to be greater in patients whose lung biopsy specimens showed a predominantly proliferative pattern of LAM lesions. Further, although airways inflammation (ie, bronchiolitis) was found in airways surrounded by heavy infiltrates of LAM cells, 9 there was no pathologic evidence of bronchial asthma, smooth-muscle hypertrophy, or any other condition that could be associated with airways disease. One must conclude that airflow obstruction in patients with LAM is related to LAM cell proliferation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These lesions promote cystic destruction of the lung and lead to loss of pulmonary function, for which there is no therapy (6). The molecular mechanisms promoting LAM cell proliferation remain largely unknown (7).…”
Section: Lymphangioleiomyomatosis (Lam)mentioning
confidence: 99%